Pengaruh Perbedaan Jenis Pakan Alami (Skeletonema sp., Chaetosceros sp., Tetraselmis sp.) terhadap Laju Pertumbuhan dan Kandungan Nutrisi pada Artemia sp. [Effect Of Different Live Feed Type (Skeletonema sp., Chaetosceros sp., Tetraselmis sp.) To The Growth Rate and Nutritional Content On Artemia sp. ] - Rahayu Kusdarwati; Muhammad Yohan Firmansyah; Yudi Cahyoko (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract Artemia is an important live feed in the hatchery. Quality of Artemia can not be separated from the feed quality that given. The quality and quantity of feed in the waters constitute factors that determine the growth rate and nutrition contentent the Artemia. This study aims to determine effect of different live feed type to the growth rate and nutritional content on Artemia sp.. The research method used was experimental with Completely Randomized Design (CRD) using four treatments and five replications. The treatments used were: silage fish (A), Skeletonema sp. (B), Chaetoceros sp. (C) and Tetraselmis sp. (D). Analysis of data uses Anova. To know the difference among the treatments were done by Duncan Multiple range test. The results showed that difference of natural feed influence highly significant (p<0,05) on the rate of growth in absolute length and significant influence (p <0,05) on average daily growth weight of Artemia sp. Absolute length growth rate was highest in treatment D (3,92mm), then a row followed by treatment C (3,275mm), A (1,89mm) and B (1,775mm). The daily growth rate of weight was highest in treatment D (25,43%), then a row followed by treatment C (21,91%), B (19,24%) and A (18,77%). . Artemia that given live feed produces highest nutritional value of D (protein 44,96%; carbohydrate 18,47% and fat 26,91%) wasted Tetraselmis sp. and the lowest obtained by treatment A (protein 41,21%; carbohydrate 8,88% and fat 29,1%) wasted silage fish. Water quality during Artemia cultivation was temperature 28-320C, pH 7, dissolved oxygen 5-8 mg/L, salinity 31 ppt and ammonia 00,25 mg/L.